Politics and Power in Multinational Companies: Integrating the International Business and Organization Studies Perspectives. Issue 9 (September 2016) - Geppert, Mike; Becker-Ritterspach, Florian; Mudambi, Ram
The study of power and politics in multinational companies (MNCs) has been a niche area of study for both scholars of organization studies (OS) and international business (IB). Further, the awareness of each research community with regard to the efforts of the other has been rather superficial. Hence, bridge-building efforts to cross-fertilize ideas developed in IB and OS in order to enhance our understanding of the nature and role of politics and power in the MNC are overdue. In order to develop the basis for integration, we trace the conceptual developments in the two disciplines, that enables us to highlight particularly promising opportunities for integrative advances. Using a typology which differentiates among four 'faces' of power in the study of management and organization, we discuss how focusing on each of these four dimensions may help us to both see and make sense of different aspects of power relations and facets of politics in MNCs. We then use the 'four faces' framework to outline how OS and IB approaches can be integrated to develop a more complete understanding of politics and power in MNCs. Finally we suggest some directions for future research.